2011
DOI: 10.1007/s11695-011-0437-7
|View full text |Cite
|
Sign up to set email alerts
|

Early Improvement in Albuminuria in Non-diabetic Patients after Roux-en-Y Bariatric Surgery

Abstract: Improvements in microalbuminuria in the early post-operative period after Roux-en-Y surgery may result from an interplay between changes in gastrointestinal hormones, insulin sensitivity, blood pressure, and adipose tissue-and needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Others have shown that even moderate weight reduction in patients with type 2 diabetes with proteinuria, reduces urine protein excretion by approximately 30% 80 . Furthermore, weight reduction achieved through either dietary caloric restriction or bariatric surgery has been shown to attenuate progression of proteinuria in obese non-diabetic individuals 8182 .…”
Section: Pathophysiology Of Obesity and Diabetes-related Kidney Diseasementioning
confidence: 99%
“…Others have shown that even moderate weight reduction in patients with type 2 diabetes with proteinuria, reduces urine protein excretion by approximately 30% 80 . Furthermore, weight reduction achieved through either dietary caloric restriction or bariatric surgery has been shown to attenuate progression of proteinuria in obese non-diabetic individuals 8182 .…”
Section: Pathophysiology Of Obesity and Diabetes-related Kidney Diseasementioning
confidence: 99%
“…Indeed, different indexes of overweight (BMI, waist to hip ratio and waist circumference) have been associated with increased albuminuria in both non-diabetic and diabetic populations [ 14 17 ]. Weight reduction has also been demonstrated to reduce albuminuria in non-diabetic obese individuals [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their outcomes could not be combined with other studies, 2 studies [ 41 , 48 ] were excluded from meta-analysis. 14 studies of 1186 patients with dichotomous data [ 21 , 23 , 24 , 26 , 27 , 29 , 32 34 , 38 , 42 , 43 , 45 , 51 ] and 10 studies of 930 patients with continuous data [ 24 , 25 , 29 , 33 , 36 , 37 , 46 , 47 , 49 , 50 ] were included in the meta-analysis of albuminuria and proteinuria. There were only 5 studies of 184 patients [ 25 , 26 , 28 , 40 , 44 ] in the review of CKD II.…”
Section: Resultsmentioning
confidence: 99%